2021
DOI: 10.31083/j.ejgo4204114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 17β estradiol (17βE) levels and Catechol -O- methyltransferase (COMT) levels in ovarian cancers

Abstract: Objectives: Epidemiological data show that induction of ovarian cancer is related to estrogen exposure and metabolism. In addition catechol metabolites of estrogen also contribute to carcinogenesis. O methylation by Catechol -O-methyltransferase is a phase II metabolic inactivation pathway for catechol estrogens. The goal of this study was to evaluate a potential correlation between COMT and 17β estradiol levels and ovarian cancer. Subjects and methods: COMT and 17βE levels were measured in ovarian tissue and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…If the metabolic clearance of hydroxylated oestrogen is slow or incomplete, reactive oxygen species may accumulate and promote the development of ovarian cancer (Goodman et al, 2001). To our knowledge, there are data showing that COMT is an important protective enzyme against neoplastic transformation in the ovary (El‐Etreby et al, 2021). In these studies, the authors observed a significant reduction in tissue and serum levels of COMT in patients with malignant ovarian tumours in comparison to the control and benign groups.…”
Section: Discussionmentioning
confidence: 99%
“…If the metabolic clearance of hydroxylated oestrogen is slow or incomplete, reactive oxygen species may accumulate and promote the development of ovarian cancer (Goodman et al, 2001). To our knowledge, there are data showing that COMT is an important protective enzyme against neoplastic transformation in the ovary (El‐Etreby et al, 2021). In these studies, the authors observed a significant reduction in tissue and serum levels of COMT in patients with malignant ovarian tumours in comparison to the control and benign groups.…”
Section: Discussionmentioning
confidence: 99%